Assessing soil respiration in the soil profile. A study case of gradient-based CO2 efflux and subsurface production rates using soil diffusion chambers - Albanito, Fabrizio (Trinity College (Dublin, Ireland). Department of Botany, 2010)
The impact of global warming on soil respiration is strongly related to the characteristics of deep-soil carbon and may differ with soil depth. Environmental parameters can affect the rates of soil CO2 respiration not only temporally at daily and seasonal scale, but also spatially in vertical and horizontal dimensions. Therefore, it is important to evaluate soil subsurface CO2 production and investigate the seasonal response of deep-soil respiration to different environmental conditions. In this respect, accurate techniques used to monitor the soil CO2 concentrations in the soil profile offer the opportunity to identify localized sources and potential sinks in the soil, and to understand the processes that control CO2 production and emission.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin